CHANGES IN MOTIVATION THAT AFFECT EMPLOYEE PERFORMANCE DURING THE COVID 19 PANDEMIC - Nilasari, B. Medina; Nisfiannoor, M.; Devinta, Florensia Rosary Meida (Universitas Brawijaya, Indonesia, 2021)
This study aims to analyze whether self-efficacy, intrinsic motivation, and extrinsic motivation can influence employee performance. The analysis was carried out using the Structural Equation Model (SEM) method using the AMOS version 24. The sample amounted to 200 people who are employees of various sectors of private companies in the Jabodetabek area. The results showed that self-efficacy led to increased employee performance. The higher self-efficacy in work, the employee performance will increase. Meanwhile, the motivation that affects employee performance is extrinsic, not intrinsic motivation. Extrinsic motivation is a mediator that strengthens the effect of self-efficacy on employee performance. The implication for the company is that the company must continue to improve the self-efficacy of employees through managers provides counseling continuously to employees in determining work goals/targets following KSA (knowledge, skills, and abilities). In addition, managers also need to assign clear, detailed, and measurable tasks to employees. In a pandemic like now, extrinsic motivation must be focused more. Various forms of extrinsic motivation that managers can do, such as: creating attractive incentive/bonus/ commission programs, giving praise to employees who have completed tasks, and giving recognition for good employee work. Further research can add variables that mediate the effect of self-efficacy on employee performance such as creativity variables, and the addition of independent variables such as transformational leadership that can affect selfefficacy, or add moderator variables such as job levels.